Acute acro-ischemia in the child at the time of COVID-19. - Mazzotta, F.; Troccoli, T. (European Journal of Pediatric Dermatology, 2020)
5 weeks after the diagnosis of the first autochthonous case of COVID-19 in Italy - February, 20 2020 - the authors reported that children and adolescents otherwise in good health were suffering from acroischemic foot lesions. The lesions, which were reminiscent of chilblains, were often painful and evolved within a few weeks with restitutio ad integrum. The lesions were probably the expression of vascular disorders related to SARS-CoV-2 infection.